Investigation of the Fitness for Service (FFS) of Cracks in API 5L X70 Pipeline Steel using Failure Assessment Diagram (FAD) - Mudjere, Kingsley; Adedipe, Oyewole; Abdulrahman, Asipita Salawu; Abolarin, Matthew Sunday (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
In this study, the fitness for service of crack propagation in API 5L X-70 stee1 was investigated using a model called Failure Assessment Diagram (FAD) to determine how fit a crack can be under certain operational pressure. It is a known fact that during the production of pipes, there are tendencies for flaws such as inclusions and cracks to occur in the pipes. When these flaws are subjected to stresses, there are tendencies for failures to occur starting from where the cracks or flaws are located. The failure due to the propagation of the cracks leads to oil spillage causing pollution to the environment which had negatively impacted livelihood of the host communities and aquatic lives. This had resulted in Government spending huge amount of money maintaining the pipelines and remediation. The purpose of this paper is to investigate the fitness for service of crack lengths 12 mm, 17 mm, 22 mm and 27 mm using the Failure Assessment Diagram (FAD) mode1. The material used in this paper is API 5L X 70 steel in the form of a Compact Tension (CT) specimen machined according to ASTM E1820 – 13. API 5L X-70 stee1 is a low-carbon stee1 with a carbon content of as low as 0.04 %. It is used in the production of pipelines for conveying crude oil and natural gas from the place of production to the place of refining or export. In the investigation of the fitness for service of the cracks, a charpy V-notch impact test was carried out to determine the energy required to fracture the steel, which was later inputted numerically into a critical stress intensity factor formula in accordance with BS 7910 – 13 standards to obtain the critical stress intensity factor (KIC or KQ). The stress intensity factor (KI) was obtained from formula also according to BS 7910 – 13 standards. The ratio of KI to KQ was used in the FAD analysis. Subsequently, a monotonic tensile test was conducted to obtain the yield stress ( ys) and the reference stress ( ref) was obtained numerically according to BS 7910 – 13. The ratio of ref) to ys) was also used in the FAD analysis. The FAD analysis was used to determine the fitness for services and fracture behaviour of each crack. Scanning electron microscopy (SEM) was used to confirm the fracture behaviour obtained from the FAD. The results obtained show that the energy from the charpy V-notch impact test was 302.9 J and the critical stress intensity factor (KQ) correlated numerically according to BS 7910 – 13 was determine as 246.73 MPa . The yield stresses obtained from the monotonic test for crack lengths of 12 mm, 17 mm, 22 mm and 27 mm were 132.51 MPa, 109.10 MPa, 114.36 MPa and 118.21 MPa, respectively. In the FAD analysis, it was observed that the safe operational stress to ensure fitness for service decreases with an increase in crack length. The fracture behaviour shows a ductile fracture behaviour since the FAD lies within the plastic collapse region. This fracture behaviour was confirmed by the image obtained from the scanning electron microscopy (SEM), which showed a cup and cone image suggesting ductile fracture behaviour. This FAD method will ensure that safe operational stresses are maintained for various crack length to prolong the life span of the pipeline. It is a novel method that can also be used to properly schedule the rate of inspection in pipelines alongside Ultrasonic sound, Liquid penetrant, Magnetic particle and radiographic methods of inspection.